3D nitrogen-doped hierarchical porous carbon framework for protecting sulfur cathode in lithium–sulfur batteries. (4th June 2019) - Song, Yan; Wang, He; Ma, Qianli; Li, Dan; Wang, Jinxian; Liu, Guixia; Yang, Ying; Dong, Xiangting; Yu, Wensheng
Abstract : A three-dimensional carbon substrate integrating a hierarchical porous network structure with rich nitrogen atom doping is designed for lithium–sulfur batteries. Abstract : Lithium–sulfur batteries are promising energy storage systems because of their high energy density and cost-effectiveness. However, their practical application is hampered due to rapid capacity degradation and low areal capacity induced by the shuttling of intermediate polysulfides and slow reaction kinetics. The host material plays a critical role in enhancing cycling stability and rate capability. Here, we reported a simple and scalable strategy to construct a rich nitrogen-doped carbon-based host with a three-dimensional (3D) hierarchical porous network and interconnected microchannels. Specifically, both channels and porous structure could be regulated by adjusting the ratio of polyacrylic acid to polyacrylonitrile in the precursor. The nitrogen-doped porous carbon network effectively suppressed the translocation of the polysulfide and triggered fast redox kinetics resulting from the fast charge transfer at the interface between the electrode and electrolyte. Taking advantage of the hierarchical porous architecture design, the nitrogen-doped porous carbon framework/sulfur composite electrode delivered high initial discharge capacity of 1228 mA h g −1 with 81.9% capacity retention and low capacity decay of 0.06% after 300 cycles. Even at a high sulfur loading of 6.5 mg cm −2, the electrode still achieved capacity retention of 65.1% and a lower capacity fading rate of 0.069% per cycle after 500 cycles at 1C. In particular, this hierarchical porous network structure opens a new avenue to develop an electrode with high energy density and long life for electric storage applications.